Estimation of China's alternative policies of automotive fuels – A perspective of oil dependence. (10th September 2017) - Jiao, Jianling; Zuo, Feifei; Li, Lanlan; Yuan, Huanxiang; Li, Jingjing
Abstract: In 2015, China's oil safety is seriously endangered with its oil dependence on imports exceeding 60% for the first time. One of the most direct and effective ways of improving oil safety is to reduce oil consumption by substituting automotive fuels. This paper, from the perspective of reducing the cost of oil dependence, constructs a conceptual model of substituting automotive fuels and an evaluation model, and studies the substitutive effects of three kinds of substitutive policies in transportation industry: natural gas, ethanol, and methanol, which have been either put into real practice or in the period of demonstration, and are attached great importance by Chinese government. The results show that the international oil price will drop after implementing the alternative fuel policies, and the absolute value of Chinese economy to oil price elasticity is smaller. The three substitutive policies can obviously reduce the cost of oil dependence, among which ethanol does the best, followed by natural gas and methanol, though the effects vary insignificantly. Taking environmental effect, resource and technology of three alternative policies as a whole, this paper suggests that China should promote natural gas alternative policy in short-term. Highlights: Alternative automotive fuels are estimated from the perspective of oil dependence. A conceptual model of effect evaluation on alternative automotive fuels is developed. Empirical study is based on an evaluation model of substitutive policies. Natural gas as substitutive auto fuels should be expanded in China in the present.